Fuel usage and estimates or air pollution emissions in the Kuala Lumpur-Petaling Jaya area Malaysia - Sham Sani, (Universiti Kebangsaan Malaysia, 1979)
On the basis of fuel usage, estimates of air pollution emissions in the Kuala Lumpur-Petaling Jaya area were attempted. This shows that Kuala Lumpur-Petaling Jaya is subject to the 'Los Angeles' type pollution. Although pollution is still generally low compared to some mid-latitude cities, marked increases in energy use, particularly petroleum products, have occurred recently. This can aggravate further the pollution situation in the study area.